STUDI HANTARAN KONDUKSI PANAS DI SEKITAR MANIFESTASI PANAS BUMI DI BAGIAN SELATAN GUNUNG TAMPUSU - Miranda Supriyadi; Donny Royke Wenas; Jeane Cornelda Rende (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
Indonesia is a country that has 40% of the world's geothermal potential, but only 3% was used.Research to determine the potential for geothermal distribution in the southern part of MountTampusu is by taking data directly using a thermometer, the purpose of this research was todetermine the temperature distribution at a depth of 0 cm, 30 cm, 60 cm, 90 cm by mapping. Thedata obtained is primary data, then entered into Microsoft Excel. In Microsoft Excel analyzed of themaximum, minimum and average temperatures. Then from the temperature data in the form oftemperature contours based on depth by using surfers 11. From the results of data processing usingsurfers, it was found that the temperature distribution in the southern part of Mount Tampusu variedin value, in the morning at depth 0 cm, 30 cm, 60 cm, 90 cm has value 23.5775°C, 22.67°C,23.315°C, 24.1025°C, daytime at depth 0 cm, 30 cm, 60 cm, 90 cm has value 27.5675°C,24.2525°C, 24.1825°C, 24.6925°C, in the evening at depth 0 cm, 30 cm, 60 cm, 90 cm has value24.5525°C, 24.3525°C, 24.2825°C, 24.605°C. The temperature pattern in the southern part ofMount Tampusu has a perpendicular pattern and slightly spreads to the northwest.